Islamic Religious Education Strategies for Strengthening Students’ Skills in Facing Moral, Social, and Educational Challenges - Husna Husna; Ahyar Rasyidi; Uria Hasnan; Muhammad Yusuf; Ahmad Nordian (Al-Mukhlashin: Jurnal Multidisiplin Ilmu, 2025)
The background that prompted writing this article was to find out learning strategies for Islamic Religious Education because learning strategies are important in achieving learning goals. This strategy is ideally chosen according to the nature or character of the subject matter itself. Islamic Religious Education is one of the mandatory subjects in school. The main aim of this subject is to equip students with the values of Islamic teachings so that students have Islamic character and are skilled in facing challenges. Religious education has its own strategies apart from the strategies commonly used in learning other subjects. Apart from that, Islamic religious studies also have a special aim in forming attitudes besides educating the mind. Meanwhile, in evaluating the success of Islamic religious learning, it is not only about assessing cognitive and psychological abilities, but also assessing attitudes is more important. This writing uses qualitative research methods and data collection techniques using library research methods.